Administrative infraction of EIA avoidance.: Criteria and effectiveness of the procedures of the Superintendency of the Environment. - Arellano Reyes, Gustavo; Chubretovic Arnaiz, Teresita (Revista de Derecho Ambiental, 2023)
Environmental Impact Assessment (EIA) avoidance is an infraction that has been primarily regulated in the Organic Law of the Superintendency of the Environment (LOSMA) and, more recently, in Law No. 21,595 on economic crimes. This study focuses on EIA avoidance as an administrative infraction (Article 35, letter b of the LOSMA) and on the procedures that the Superintendency of the Environment (SMA) uses to address it. The SMA employs two discretionary procedures to address this infraction: a regular punitive procedure and a special procedure known as “requirement for submitting to EIA”. Both procedures serve different purposes: the first aims to impose a sanction (with a punitive and deterrent objective), while the second aims to ensure compliance with regulation by subjecting avoidant activities to EIA without imposing a penalty (with a corrective objective). This discretionary power has been recognized by jurisprudence based on the administrative principles of opportunity, efficiency, and effectiveness. The objective of this study is to analyze the value of the requirement for submitting to EIA procedure. This, from the perspective of achieving its corrective purpose and to assess whether it can serve the broader interests of the SMA's supervisory work. It questions whether it is acceptable to solely demand the submission of a project in avoidance to EIA, mitigating the punitive function and its deterrent effect regarding this kind of infraction.